James Hogg and The Unfathomable Hell - Jackson, Richard (Romanticism on the Net, 2002)
AbstractThe use of opium, often in the form of laudanum, was a constituent element of the Romantic Imagination. Coleridge, Thomas De Quincey, and Charles Lloyd were all subject to its bondage. In Scotland the literati of Blackwood’s Edinburgh Magazine were aware of its prevalence. James Hogg had a ‘perfect horror’ of the effects of laudanum and gave great offence to John Gibson Lockhart when, in his Anecdotes of Sir W. Scott, he revealed that Lady Scott had taken opium. In one of the ‘Noctes Ambrosianae’ published in Blackwood’s, probably written by John Wilson (himself possibly an opium user) Hogg’s persona, accompanied by De Quincey, also a Blackwood’s contributor, speaks eloquently about its horrid effects. Hogg parodied Coleridge’s poetry and was familiar with the unfathomable hell into which opium’s usage plunged its ‘eaters’. The nightmarish experiences of Robert Wringhim in Hogg’s Private Memoirs and Confessions of a Justified Sinner reflect those of Coleridge and Lloyd and their devilish sense of confusion of identity and insane impulses. Hogg would also be aware of The Stranger’s Grave written by George Gleig, another frequent Blackwood’s contributor. He returned to the self-persecuting theme of the doppelganger in his story called Strange Letter of a Lunatic.